Array-Patterned Micro-Structures in Spectacle Lenses Designed for Myopia Control via Image Blur - Huilv Jiang; Zengwei Zhao; Quan Yuan; Yiqian Li; Ke Ma; Yaoyao Fu; Jiaojie Chen; Jun Jiang; Yiyu Li (Photonics)
Using micro-structure components in spectacle lenses has enabled myopia progression control in children and teenagers. However, the optical design of these spectacle lenses has never been discussed, leading to a lack of correct understanding of the underlying optical treatment principles. In this work, array-patterned hexagonal lenslets with two powers of opposite signs were proposed to construct a lenslet array-integrated (LARI) spectacle lens developed for an ongoing, randomized, controlled clinical trial and to support the optical approach to myopia control leveraging retinal image blur. We found that the phase modulation induced by the micro-structures of the lenslet array contributes to the increase in RMS wavefront aberrations, leading to image blur, further inspiring the novel array-patterned micro-structure design with high-order phase elements (HOPEs). The optical performance of both LARI and HOPE spectacle lenses was investigated by simulation and experiment.